Effect of biodegradable Zn screw on bone tunnel enlargement after anterior cruciate ligament reconstruction in rabbits. (September 2021) - Mao, Genwen; Wang, Chang; Feng, Meng; Wen, Binbin; Yu, Sen; Han, Xuezhe; Yu, Zhentao; Qiu, Yusheng; Bian, Weiguo
Graphical abstract: Highlights: It was the first time to reveal that zinc screw-released element effectively attenuated bone tunnel enlargement after anterior cruciate ligament reconstruction in rabbits. Implant-released zinc upregulated sodium vitamin C transporter 2 in primary osteoblasts through the nuclear factor of kappa B pathway, which ultimately triggered the osteogenic differentiation. It laid the foundation for the deployment of biodegradable zinc metallic materials for anterior cruciate ligament rupture patients. Abstract: Zn and its alloys have recently emerged as new options for orthopedic implants due to their desirable biodegradation rate and mechanical strength. However, whether Zn metallic implants attenuate bone tunnel enlargement (BTE) after anterior cruciate ligament (ACL) reconstruction and, if so, the underlying mechanism by which this occurs remains elusive. In present study, we explored the possibility of using pure Zn screws to attenuate BTE in rabbits, and the potential molecular mechanism was further explored in primary osteoblasts. Here, our study showed that the pure Zn screws more effectively attenuated BTE after ACL reconstruction in rabbits compared with pure Mg and Ti screws. This was attributed to the fact that the pure Zn screw-released Zn element diminished the size of the femoral tunnels, enhanced the bone mass around the screws, boosted the fixation strength, and promoted the tendon-bone integration. Several lines of cellular evidences suggested that Zn metallic implant-released Zn element induced upregulation of sodium-dependent vitamin C transporter 2 in primary osteoblasts and ultimately elevated the expressions of the osteogenic transcription factors to trigger osteogenic differentiation. This study showed that biodegradable Zn metallic materials were promising candidates for interference screw to attenuate BTE after ACL reconstruction.